THE LEADERSHIP ROLE OF CHIEF MADRASAH IN DEVELOPING CHARACTER EDUCATION IN ISLAMIC SCHOOLS IN INDONESIA - Badrun (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This research is aimed at identifying the role of leadership to schools in developing character education in Islamic schools in Indonesia. Madrasah as an educational container with religious characteristics (Islam) aims to produce outputs of pupils with character based on Islamic values. The power of the educator/teacher as a spearhead in the formation of the character of the student, and the head of the madrasah has a very important role in the development of character education, especially in the movement and coordination of all the potential, and educational resources available. This research seeks to: (1) analyze and describe the role of the head of the madrasah in developing character education, (2) describe character education implementation, and (3) describe developmental character education values. The type of research used is qualitative research with descriptive design. The study was conducted in several Islamic schools in Indonesia. Data analysis is performed interactively and continuously until the data is saturated. Activities in data analysis using the Miles and Huberman models are data reduction, data display, and conclusion drawing/verification. The results of this research show that: First, the role of the head of the madrasah in the development of character education as the formulator of the character education program (Manager), second. the head madrasha acts as the builder of character Education (Educator) as a reference in the application of character learning (Modelling).